Acetylene Dithiolate Linking up the [Tp′W(CO)(CN)] Moiety with RuII or PdII. Issue 43 (11th September 2013) - Seidel, Wolfram W.; Dachtler, Woldemar; Semmler, Julia; Tänzler, Marco; Folk, Manuel; Villinger, Alexander
Abstract A series of heterodinuclear complexes with acetylene dithiolate (acdt2−) as the bridging moiety were synthesised by a facile one‐pot procedure that avoided use of the highly elusive acetylene dithiol. Generation of the W–Ru complex [Tp′W(CN)(CO)(C2S2)Ru(η5‐C5H5)(PPh3)] (Tp'=hydrotris(3, 5‐dimethylpyrazolyl)borate) and the W–Pd complexes [Tp′W(CN)(CO)(C2S2)Pd(dppe)] and [Tp′W(CO)2(C2S2)Pd(dppe)][PF6] (dppe=1, 2‐bis(diphenylphoshino)ethane), which exhibit a [W(η2‐κ2‐C2S2)M] core (M=Ru, Pd), was accomplished by using a transition‐metal‐assisted solvolytical removal of the Me3Si‐ethyl thiol protecting groups. All intermediate species of the reaction have been fully characterised. The highly coloured W–Ru complex [Tp′W(CN)(CO)(C2S2)Ru(η5‐C5H5)(PPh3)] shows reversible redox chemistry, as does the prototype complex [Tp′W(CO)2(C2S2)Ru(η5‐C5H5)(PPh3)][PF6]. Single crystal X‐ray diffraction and IR, EPR and UV/Vis spectroscopic studies in conjunction with DFT calculations prove the high electronic delocalisation of states over the acdt2− linker. Comparative studies revealed a higher donor strength and more pronounced dithiolate character of acdt2− in [Tp′W(CN)(CO)(C2S2)Ru(η5‐C5H5)(PPh3)] relative to [Tp′W(CO)2(C2S2)Ru(η5‐C5H5)(PPh3)]+. In addition, the influence of the overall complex charge on the metric parameters was investigated by single‐crystal X‐ray diffraction studies with the W–Pd complexes [Tp′WL2(C2S2)Pd(dppe)] (L=(CN−)(CO) or (CO)2). The central [W(C2S2)Pd] units exhibit high structural similarity, which indicates the extensive delocalisation of charge over both metals.